Abnormal perfusion fluctuation and perfusion connectivity in bipolar disorder measured by dynamic arterial spin labeling. (29th October 2019) - Dai, Weiying; Chen, Mingzhao; Duan, Wenna; Zhao, Li; Bolo, Nicolas R.; Tamminga, Carol; Clementz, Brett A.; Pearlson, Godfrey D.; Alsop, David C.; Keshavan, Matcheri
Abstract: Objectives: We sought to evaluate whether dynamic Arterial Spin Labeling (dASL), a novel quantitative technique robust to artifacts and noise that especially arise in inferior brain regions, could characterize neural substrates of BD pathology and symptoms. Methods: Forty‐five subjects (19 BD patients, 26 controls) were imaged using a dASL sequence. Maps of average perfusion, perfusion fluctuation, and perfusion connectivity with anterior cingulate cortex (ACC) were derived. Patient symptoms were quantified along four symptom dimensions determined using factor analysis of the subjects from the Bipolar and Schizophrenia Network on Intermediate Phenotypes (BSNIP) study. Maps of the perfusion measures were compared between BD patients and controls and correlated with the symptom dimensions in the BD patients only by voxel‐level and region‐level analyses. Results: BD patients exhibited (i) significantly increased perfusion fluctuations in the left fusiform and inferior temporal regions ( P = .020, voxel‐level corrected) and marginally increased perfusion fluctuations in the right temporal pole and inferior temporal regions ( P = .063, cluster‐level corrected), (ii) significantly increased perfusion connectivity between ACC and the occipitoparietal cortex ( P = .050, cluster‐level corrected). In BD patients, positive symptoms were negatively associated with ACC perfusion connectivity to the right orbitofrontal and superior frontal regions ( P = .002, cluster‐level corrected) and right orbitofrontal and inferior frontal regions ( P = .023, cluster‐level corrected). Conclusion: The abnormal perfusion fluctuations and connectivity alterations may underlie the mood fluctuations and cognitive and emotional dysregulation that characterize BD.